Waters and groundwater reservoirs at the Hannukainen mine development site in Kolari, Northern Finland - Nurminen, Tiina (Helsingfors universitet, 2013)
Hannukainen is an old mining area, at commune of Kolari in western Finnish Lapland. Rautaruukki Oy and Outokumpu Oy mined iron, copper and cold from the area in 1978 - 1990. Area is located in the Pajala-Kolari shear zone. Kaunisvaara mining project at Sweden is related to the same shear zone. Northland Mines Finland Oy is planning to restart mining of IOCG-type ore at Hannukainen area within the next couple of years. Quaternary deposits or water resources in Hannukainen area has not been examined in detail before. The mine development site is surrounded be three rivers, Valkeajoki in east, Kuerjoki in west and Äkäsjoki in south. The stratigraphical and hydrostratigraphical field studies in Hannukainen area were made in summer 2011. Stratigraphy of the Quaternary deposits was observed from the sections of Laurinoja open pit and from test pits dug to the area. Permeability of the sediment units were measured by using ring infiltration tests and calculated from grain size evaluations made from sediment samples. Groundwater was observed by evaluating the quality and representativeness of the groundwater monitoring wells, groundwater level measurements and also laboratory analyzes of main ions, trace-elements and isotope ratios of oxygen and hydrogen. In addition to chemistry samples, electric conductivity, pH, temperature and ratio of oxygen was measured with YSI multielectrode probe from rivers and open pit ponds. Groundwater - surface water interactions were observed by taking chemistry samples, measuring river bed temperatures and by installing minipiezometers. Quaternary deposits are mostly glaciofluvial and fluvial sands and gravels instead of tills. Sorted sandy sediments related to the braided river bars formed by Muonio Ice lake spillways are found from the present valleys of River Äkäsjoki, Valkeajoki and Kuerjoki. Sand and gravel sediments have good permeability and they host considerable amounts of water. Fine sediment units are thin and as discontinuous layers they host perched groundwater and confined ...